Evaluating environmental DNA metabarcoding as a survey tool for unionid mussel assessments. (23rd June 2022) - Marshall, Nathaniel T.; Symonds, Daniel E.; Dean, Cheryl A.; Schumer, Gregg; Fleece, William Cody
Abstract: Freshwater unionid mussels are a taxa‐rich group of bivalves that play a critical role in maintaining freshwater ecosystems, but are heavily imperilled due to anthropogenic influences. Environmental DNA (eDNA) provides potential benefits for the monitoring of unionids through higher detection sensitivity, lower costs, less intrusion on the environment, and added advantages for sampling challenging and remote habitats. We compare an extensive mussel rescue survey conducted as part of the demolition of a dam with the detection of mussels using eDNA metabarcoding. The unique mussel rescue survey provided a rare opportunity for an in‐depth analysis of unionid eDNA detection across both small sampling cells and a large sampling region. Environmental DNA detected 22 of the 24 (91.67%) species sampled in the rescue survey, with the two absent species found as only single individuals. A species missed by the rescue survey was detected with eDNA ( Potamilus alatus ), along with hidden cryptic diversity within the genus Pyganodon . Both survey methods detected the presence of two federally listed species from multiple sampling cells ( Plethobasus cyphyus and Theliderma cylindrica ) . Furthermore, eDNA provided similar estimates of relative mussel abundances across the sampling region. Estimates of mussel diversity were similar between the two methods, and eDNA successfully detected the two federally listed species present. These results contribute to the growing knowledge of eDNA‐based biological assessments and provide valuable insight into comparing sampling effort and detection rates from conventional and eDNA survey methods. As eDNA collection can widen the traditional sampling season and improve the ability to sample difficult or dangerous environments, these results demonstrate the practicality of eDNA metabarcoding as a supplemental sampling method to describe diverse mussel communities and improve the detection of threatened and endangered species.